2012
DOI: 10.1016/j.bbamem.2011.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Connexins in wound healing; perspectives in diabetic patients

Abstract: Skin lesions are common events and we have evolved to rapidly heal them in order to maintain homeostasis and prevent infection and sepsis. Most acute wounds heal without issue, but as we get older our bodies become compromised by poor blood circulation and conditions such as diabetes, leading to slower healing. This can result in stalled or hard-to-heal chronic wounds. Currently about 2% of the Western population develop a chronic wound and this figure will rise as the population ages and diabetes becomes more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 119 publications
2
96
0
Order By: Relevance
“…The structure and function of connexins in the skin has been highlighted in several recent review articles [4,[24][25][26][27][28], which detail different aspects of their roles particularly in hyperproliferative skin disorders, inflammation and wound healing events. The study of pannexins in skin is an emerging field, but the reader is directed to reviews on pannexins [13,16] and research papers examining the roles of pannexins in skin [17,29].…”
Section: Introductionmentioning
confidence: 99%
“…The structure and function of connexins in the skin has been highlighted in several recent review articles [4,[24][25][26][27][28], which detail different aspects of their roles particularly in hyperproliferative skin disorders, inflammation and wound healing events. The study of pannexins in skin is an emerging field, but the reader is directed to reviews on pannexins [13,16] and research papers examining the roles of pannexins in skin [17,29].…”
Section: Introductionmentioning
confidence: 99%
“…However, increased levels of Cx43 have been detected in pathological conditions, e.g. during wound healing in diabetic rats and humans (62)(63)(64). Consequently, cell metabolism and Cx43 appear to be interconnected.…”
Section: Fig 2 Cx43-nuclear and Perinuclear Interactorsmentioning
confidence: 99%
“…The inhibition of Cx43 by ASODNs has been shown to dampen inflammatory responses and promote wound-healing in many tissues including central nervous system [71], skin [72][73][74], skeletal muscle [75], heart [76], smooth muscle [77,78] and vascular endothelium [79][80][81]. Moreover, there are clinical trials using topical application of a gel containing Cx43 AS-ODNs, which have shown a safe and tolerable treatment of skin wounds, venous leg ulcers and diabetic foot ulcers [71].…”
Section: Connexin43 As a Therapeutic Target Against Ckdmentioning
confidence: 99%